EFEKTIVITAS METODE PEMBELAJARAN READING GUIDE DALAM PENINGKATAN DAYA INGAT ANAK SLOW LEARNER - Mohammad Bagas Nur Cahyo; Isroul Zamzami Fauziyah; Aisyah Salwa Dinda Aulia; Mintowati (Jurnal PENEROKA, 2025)
This study aims to determine the effectiveness of the Reading Guide method in improving the memory of slow learners who have difficulty reading. The scope of the study includes the characteristics of slow learners, the learning process, and the supporting and inhibiting factors of this method. The study used a qualitative descriptive approach with secondary data from the YouTube Channel video "Belajar Peduli" which documented the learning of slow learners using the Reading Guide method. Data were analyzed using content analysis techniques. The results showed that slow learners took longer to remember, had short concentration, had difficulty understanding complex processes, and needed a gradual approach. The Reading Guide method effectively improved memory through structured stages (pre-reading, during-reading, post-reading), repetition of information, and visual strategies. Interesting facts show the importance of teacher involvement and interactive materials. This study recommends development methods through teacher training, technology integration, and school-parent collaboration.